(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Reading skills are essential in developing other skills, not only in the language program but also in other human endeavors. It plays an important part in building a good self-image. It is a function that is necessary for today’s society. This prompted the researcher to determine the effectiveness of a multilingual reading text as a language bridging tool to develop the reading literacy skills of Grade 4 learners. This study utilized the one-group pre-test-post-test design, with the Grade 4 learners in Baccuit Elementary School in the La Union Schools Division. The researcher utilized the Philippine Informal Reading Inventory (Phil-IRI) Materials as the main data gathering tool after permission was granted by the Department of Education through the La Union Schools Division Office. The data gathered were treated using descriptive and inferential statistics. The results of the study showed that the respondents registered a frustration level in word recognition, instructional in reading speed, and independent in reading comprehension during the pre-intervention phase. In the post-intervention phase, the word recognition, reading speed, and reading comprehension of the respondents accelerated to an independent reading level. Exploring further the results, it was established that a significant difference in the reading profile favoring the post-intervention phase was observed, which led the researcher to conclude that the reading intervention employed was effective. This study provided further literature on the importance of the mother tongue in developing literacies easier in another language. It was recommended though that further replications of the study shall be conducted to validate the findings of the study while the developed reading skills bridging tool for Grade 4 learners is strongly recommended for adoption.